MACROMEDIA FLASH TO DEVELOP MATHEMATICS LEARNING MEDIA ON THE MATERIAL OF POLYHEDRON (International Conference on Social and Islamic Studies, 2022)
This study aims to determine the process of developing mathematics learning media in a valid, practical, and effective material of polyhedron. This research used Research and Development (R&D) with Analysis, Design, Development, Implementation, Evaluation model. The developed product was mathematics learning media using the Macromedia Flash application, then tested on students. The collecting data techniques used in this study were questionnaires, observation, and learning outcomes tests. The instruments used were expert validation sheets, teacher and student questionnaires, and student learning outcomes tests. The data analysis technique used was descriptive data analysis. Based on the validation results from experts related to instructional media, teacher and student response questionnaires and learning outcome tests were categorized as very valid. Referring to the analysis of teacher and student responses, they generally gave positive responses, which means that this learning media was considered practical. In addition, the average test result of student learning fulfilled the minimum completeness criteria, so it was assumed to be effective. Thus, interactive learning media using the Macromedia Flash application was considered valid, practical, and effective.